Dubbing English edutainment: Localizing educational content for Arab children - Saed, Hadeel; Haider, Ahmad S; Abu Tair , Sausan; Darwish , Noor (Research Journal in Advanced Humanities, 2024)
The translation process of any piece of media is affected by the genre and target audience. Edutainment is a genre that combines education and entertainment for young viewers. The educational materials could include mathematics, science, zoology, language, and life skills and manners. The three investigated shows in this study are Ready Jet Go and its Arabic dubbed version aired on MBC3; Wild Kratts and its Arabic dubbed version aired on Al-Jazeera Kids and Zaatar; and Martha Speaks and its Arabic dubbed version aired on Al-Jazeera Kids. This study examined whether the translations captured the different elements of children’s edutainment programs, including educational and entertainment value, by comparing the original and translated versions. The analysis showed that the nature of edutainment programs posed a challenge to the translators, as not all of their content was conveyed fully or accurately. The issues in translation include translation loss through oversimplification, substitution, untranslatability, and linguistic and cultural differences. The study concludes that since this genre combines teaching with fun for young audiences, it may pose challenges to the translator, who must balance and maintain all the shows’ different aspects while managing cultural and linguistic differences.